Synthesis, characterization, EPR, electrochemical, and in situ spectroelectrochemical studies of salen-type oxovanadium(IV) and copper(II) complexes derived from 3,4-diaminobenzophenone - KOCA, ATIF (TAYLOR & FRANCIS LTD, 2013)
A new half unit and some new symmetrical or asymmetrical VO(IV) and Cu(II) complexes of tetradentate ONNO Schiff base ligands were synthesized. The probable structures of the complexes have been proposed on the basis of elemental analyses and spectral (IR, UVVis, electron paramagnetic resonance, ESI-MS) data. VO(IV) and Cu(II) complexes exhibit square pyramidal and square-planar geometries, respectively. The complexes are non-electrolytes in dimethylformamide (DMF) and dimethylsulfoxide. Electrochemical behaviors of the complexes were studied using cyclic voltammetry and square wave voltammetry. Half-wave potentials (E-1/2) are significantly influenced by the central metal and slightly influenced by the nature of substituents on salen. While VO(IV) complexes give VOIV/VOV redox couples and a ligand-based reduction process, Cu(II) complexes give only a ligand-based reduction. In situ spectroelectrochemical studies were employed to determine the spectra of electrogenerated species of the complexes and to assign the redox processes. The g-values were calculated for all these complexes in polycrystalline state at 298K and in frozen DMF (113K). The evaluated metalligand bonding parameters showed strong in-plane sigma-bonding for some Cu(II) complexes.
Keywords: Schiff base; Metal complexes; 3; 4-Diaminobenzophenone; Electrochemistry; Spectroelectrochemistry; EPR; SCHIFF-BASE COMPLEXES; ELECTRON SPIN RESONANCE; STRUCTURAL-CHARACTERIZATION; ASYMMETRIC OXIDATION; CRYSTAL-STRUCTURES; SPECTROSCOPIC CHARACTERIZATION; AEROBIC EPOXIDATION; CATALYTIC-ACTIVITY; SULFIDE OXIDATION; VANADIUM COMPLEX